2023
DOI: 10.3389/feduc.2023.1130952
|View full text |Cite
|
Sign up to set email alerts
|

Causes of academic dropout in higher education in Andalusia and proposals for its prevention at university: A systematic review

Abstract: IntroductionOne of the main problems facing the university system is the high student dropout rate due to a number of variables, accentuated by the COVID-19 pandemic. This is a problem not only in Spanish universities but is prevalent worldwide. It is therefore important to understand and analyze the underlying reasons for dropout so that it can be addressed and mechanisms implemented to limit dropout in higher education to the greatest extent possible.MethodA systematic review was carried out summarizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…We have the factor "Academic" as the main factor of desertion; the predominant variables are: academic performance, the complexity of some courses, previous knowledge; these findings have similarity with those found by Rodriguez-Hernández et al, 2020, where he points out that the variable is academic performance, similarly, Aina et al, 2022 referring the valuation to this factor, for the interpretation of this phenomenon. Some other factors such as "Individual" are also of concern, occupies the second place, they are the student's own conditions, the variables found correspond to the student's motivation, insecurity, family and emotional problems, health; these findings are also related to the researchers De la Cruz-Campos et al (2023;Liza & García-Salirrosas, (2022), also consider the new environment, new challenges, adding the Covid-19 pandemic as another variable for desertion, these authors also mention the "economic" factor in their studies. The factor "Institutional" we have Lorenzo-Quiles et al (2023), who mentions that institutional policies, support for the student body in academics are determinants for the detention of students, there are also other variables, as noted by Mellado et al, 2018.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have the factor "Academic" as the main factor of desertion; the predominant variables are: academic performance, the complexity of some courses, previous knowledge; these findings have similarity with those found by Rodriguez-Hernández et al, 2020, where he points out that the variable is academic performance, similarly, Aina et al, 2022 referring the valuation to this factor, for the interpretation of this phenomenon. Some other factors such as "Individual" are also of concern, occupies the second place, they are the student's own conditions, the variables found correspond to the student's motivation, insecurity, family and emotional problems, health; these findings are also related to the researchers De la Cruz-Campos et al (2023;Liza & García-Salirrosas, (2022), also consider the new environment, new challenges, adding the Covid-19 pandemic as another variable for desertion, these authors also mention the "economic" factor in their studies. The factor "Institutional" we have Lorenzo-Quiles et al (2023), who mentions that institutional policies, support for the student body in academics are determinants for the detention of students, there are also other variables, as noted by Mellado et al, 2018.…”
Section: Discussionmentioning
confidence: 84%
“…Several previous review studies on student dropout have been found; for example, from an international point of view, they indicate that there are high levels of students who drop out of Spanish universities, within the first year (De la Cruz-Campos et al,2023;Lorenzo-Quiles et al,2023; as well as in other countries worldwide (Aina et al,2022;Rodríguez-Hernández et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the negative influences of isolation due to the COVID-19 pandemic have made self-learning more difficult. On a global scale, some students even failed to complete their studies for these objective reasons [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Así, la interacción con las y los compañeros se volvió más complicada de lo habitual (Browning, et al, 2021), siendo una dificultad que afecta especialmente a los estudiantes de primer año (Morosanu et al, 2010) y relacionada con el número de abandonos en los primeros años de universidad (Motl, et al, 2018). En este sentido, influyó en la pérdida de interés por los estudios, la falta de motivación hacia las metas académicas y el número de abandonos (Álvarez-Pérez, et al, 2021;de la Cruz-Campos, et al, 2023).…”
Section: Introducción Del Problema O Asunto De Investigaciónunclassified